The role of public relations in handling communication crises in public institutions - Asfar, Andi Hasryningsih; Cintana, Dea; Mahwi, Shelina; Amanda , Amanda; Zakia, Mikail Rizqi; Alamsyah, Muhammad Ghondur (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
This study aims to analyze the role of public relations (PR) in handling communication crises in public institutions. The focus of the study includes the communication strategies implemented, the effectiveness of messages delivered to the public, and the challenges faced in maintaining public trust during crisis situations. The research method used a qualitative approach with in-depth interviews and document analysis in several public institutions experiencing communication crises. The results show that the success of crisis management is greatly influenced by the ability of PR to build fast, accurate, and transparent communication. A planned communication strategy, information transparency, and good internal coordination have been proven to be able to reduce the negative impact of crises and restore the image of public institutions. The findings also reveal that the greatest challenges for PR lie in limited communication resources and internal resistance to changes in communication strategies during crises. Based on these findings, it can be concluded that the role of PR is not only to convey information, but also as a strategic actor that determines the success of public institutions in overcoming communication crises and maintaining public trust. Therefore, strengthening the capacity and professionalism of PR is a crucial factor in ensuring the communication resilience of public institutions in the future.